(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study aims to provide insights into consumer awareness, attitudes, and behavioural tendencies toward sustainable packaging, contributing to a better understanding of evolving preferences in the fast-moving consumer goods (FMCG) sector and offering implications for marketers and policymakers promoting environmentally responsible consumption. The research adopts a quantitative, descriptive, and cross-sectional design focusing on consumers in the urban context of Chandigarh. The target population includes individuals aged 18 years and above who regularly purchase FMCG products such as packaged food, personal care, and household items. Data were collected using a non-probability purposive sampling technique from 200 respondents through online and offline modes. After data cleaning, 144 valid responses were retained for analysis. A structured questionnaire was used, comprising three sections: demographic profile, awareness and perception of sustainable packaging, and behavioural practices related to eco-friendly packaging. The items were measured on a five-point Likert scale, adapted from established instruments and tailored to the Indian context. A pilot study was conducted to ensure clarity and reliability of the instrument. Internal consistency was assessed using Cronbach’s alpha, with a threshold value of 0.70 considered acceptable. The findings of the study are expected to provide valuable insights into consumer perspectives on sustainable packaging and support strategic decision-making for promoting environmentally sustainable practices in the FMCG sector.